Ocorrência de leucose enzoótica bovina na microrregião da Serra de Botucatu - Megid, Jane [UNESP]; Nozaki, C.N. [UNESP]; Kuroda, R.B.S. [UNESP]; Cruz, T.F. [UNESP]; Lima, K.C. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2003)
The aim of this study was characterize the positivity of the bovine leukosis virus in the Microregion of the Serra de Botucatu. Sera from 1193 bovine from 65 properties of the Microregion of the Serra de Botucatu were evaluated throught ELISA test. All the evaluated animals were adult and 16 of them only were male; 85.5% were crossbred, 6.45% Nellore and 8% dutch. of the analyzed samples, 618 sera had resulted positive to the test. In only one flock it was not found seroreagents animals, the regional positivity was 52% (the seropositivity in the properties varied of 10% to 67%), the higher the percentage of positivity was in the animals of the dutch race (94.7%), followed for the crossbred (43.7%). The high percentage of positivity of the disease in our region is distinguished.
Occurrence of bovine leukosis virus in the microregion of the Serra de Botucatu, SP, Brazil
Keywords: bovino; leucose enzoótica; Botucatu; bovine leukosis virus; Botucatu; ELISA